STYLISTICS AND FIGURATIVE LANGUAGE IN SUE MONK KIDD’S THE SECRET LIFE OF BEES:: A STYLISTICS ANALYSIS - Fais Wahidatul Arifatin (Journey: Journal of English Language and Pedagogy, 2019)
The goals of this study are to find out kinds of figurative language used by Sue Monk Kidd in his novel, The Secret Life of Bees, to investigate how the artistic effect and linguistic evidence achieved through figurative language and to describe how figurative language supports the theme. The research deals with the use of figurative language in a literary work, novel. Hence, this study contains the figurative language and also Sue Monk Kidd’s stylistics. The Secret Life of Bees was a New York Times bestseller list, it won 2004 book sense book of the year awards, and it was nominated for the orange broadband prize for fiction. This novel also adapted to film directed by Gina Prince-bythewood. The writer found that dialect as a stylistic is merely one way to build characterization; Kidd is adept at several others including the art of conversation, the art of story-telling, and the art of description in ekspressing the main character. While the figurative language found in this research are simile, personification, metaphor, symbolism, imagery and allegory.